2012
DOI: 10.1016/j.cllc.2012.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Direct Comparison of 3 PCR Methods in Detecting EGFR Mutations in Patients with Advanced Non–Small-Cell Lung Cancer

Abstract: Micro abstractWe compared three PCR methods (mutant-enriched PCR, PNA-LNA PCR and PCR clamp) to detect EGFR mutations in 50 patients with advanced NSCLC. Seventeen were harboring EGFR mutations, five of whom showed discrepancies between the results of different PCR methods. All five responded to gefitinib, which we consider to suggest that the discrepancies were false negatives. Clinical Practice Points• Several methods have been used to detect EGFR mutations in non-small-cell lung cancer (NSCLC): however, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 29 publications
1
8
0
2
Order By: Relevance
“…27 In the present study, the sensitivity of the mutant-enriched PCR method was not inferior to the PNA-LNA PCR and PCR clamp methods. 29 They also analyzed intra-tumor heterogeneity without considering the pathological patterns. We considered that the intra-tumor heterogeneity could be demonstrated by an analysis in accordance with the pathological pattern of mixed-type adenocarcinoma in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…27 In the present study, the sensitivity of the mutant-enriched PCR method was not inferior to the PNA-LNA PCR and PCR clamp methods. 29 They also analyzed intra-tumor heterogeneity without considering the pathological patterns. We considered that the intra-tumor heterogeneity could be demonstrated by an analysis in accordance with the pathological pattern of mixed-type adenocarcinoma in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…0.1 %) [9]. The reliability of PNA–LNA PCR clamp has been also confirmed in clinical settings, with high sensitivity (97 %) and specificity (100 %) demonstrated in variety of cytological specimens (bronchoscopy samples, sputum, pleural and pericardial effusion) in addition to paraffin-embedded tissues [1, 24, 26]. Accordingly, Yamada et al [24], demonstrated that the PNA–LNA PCR clamp method allowed positive diagnosis in 33.6 % of 122 cytological samples from Asian NSCLC patients .…”
Section: Discussionmentioning
confidence: 96%
“…Previously, we demonstrated that the median concentration of DNA isolated from intrabronchial forceps biopsy is 38.3 ng/μl [19]. However, commercially available in vitro diagnostic real-time PCR-based tests (CE-IVD) specifically designed for of the detection of EGFR activating mutations are not validated to analyse samples with less than 150–800 ng of DNA or 10 % of neoplastic cells [2, 5, 25, 26]. Thus, the development of highly sensitive molecular methods appropriate for more technically demanding samples has become a major focus in lung cancer diagnostics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The techniques currently used to identify EGFR mutations in patients with lung cancer include PCR single-strand conformation polymorphism, 22 high-resolution melting analysis, 23 ARMS technology, 24 mutant-enriched PCR, peptide nucleic acid-locked nucleic acid PCR clamping, 25 and direct sequencing. These methods come with distinct advantages and disadvantages.…”
Section: Discussionmentioning
confidence: 99%